INTEGRASI PRINSIP SUPERVISI PENDIDIKAN DAN NILAI ISLAM DALAM AL-QUR’AN DAN HADIS - Saifullah, Saifullah; Elistatia, Usi; Septia, Rizka; Subandi, Subandi; Dermawan, Oki (STKIP Pesisir Selatan, 2025)
This study aims to comprehensively analyze the integration of educational supervision principles with Islamic values derived from the Qur’an and Hadith. Educational supervision plays a strategic role in improving learning quality, teacher performance, and professional development. However, in practice, supervision is often reduced to administrative and technical activities, thereby neglecting its moral and spiritual dimensions. From an Islamic perspective, supervision is understood as a continuous developmental process grounded in the values of amar ma’ruf nahi munkar, shūrā (consultation), muraqabah (self-awareness before God), amanah (responsibility), and iḥsān (continuous improvement). This research employs a qualitative method with a library research approach, examining primary sources such as the Qur’an, Hadith, and classical as well as contemporary tafsir, along with secondary sources including relevant books and scholarly articles. Data analysis was conducted using a descriptive-analytical method to explore the relationship between modern educational supervision concepts and Islamic values. The findings indicate a strong alignment between supervision principles such as guidance, participation, objectivity, and sustainability and Islamic values of justice, honesty, responsibility, and continuous improvement. This integration results in an Islamic educational supervision model that positions supervisors as both professional and spiritual mentors in fostering an educational work culture grounded in faith, knowledge, and ethical practice.